Meningkatkan Keterampilan Siswa Dalam Mengapresiasi Unsur-Unsur Intrinsik Cerita Pendek Dengan Menerapkan Metode Cooperative Integrated Reading And Composition (CIRC) - Guru SMK Negeri 1 Klaten, Suhirna (Teknis, 2017)
The purpose of this study is to improve the students skills in appreciating the short story in the students of class XI MM 1 SMK Negeri 1 Klaten in 2017 / 2018. The subject of the research is the students of class XI MM 1 SMK Negeri 1 Klaten which is 35 students. Data collection techniques are observation / observation and written test. The research used cycle twice as many as cycle I and II with planning, action, observation and reflection. Data analysis technique using percentage and mean then compared / yield compared to each cycle. The results showed that through the implementation of cooperative learning model of Cooperative integrated reading and Composition (CIRC) model can improve students learning achievement on competency standard "literary elements of literature" for students of class XI MM 1 SMK Negeri 1 Klaten in the even semester of 2017 / 2018. This is shown by the results of the discussion: which shows the increase in yield from cycle to cycle as follows: The lowest value increases 50% Â from 40 to 80, the highest value increases 5.5% from 85 to 95, the mean value increases 24% from 65.2 to 85 , 53 and the completeness rose from 82% Â to 100%.Keyword : Short story Appreciation, Cooperative Integrated Reading and Com position Method.